Indoor Radio Measurement and Planning for UMTS/HSPDA with Antennas - (:unkn) unknown (My University, 2013)
Over the last decade, mobile communication networks have evolved tremendously with a key focus on providing high speed data services in addition to voice. The third generation of mobile networks in the form of Universal Mobile Telecommunications System (UMTS) is already offering revolutionary mobile broadband experience to its users by deploying High Speed Downlink Packet Access (HSDPA) as its packet-data technology. With data speeds up to 14.4 Mbps and ubiquitous mobility, HSDPA is anticipated to become a preferred broadband access medium for end-users via mobile phones, laptops etc. While majority of these end-users are located indoors most of the time, approximately 70-80% of the HSDPA traffic is estimated to originate from inside buildings. Thus for network operators, indoor coverage has become a necessity for technical and business reasons. Macro-cellular (outdoor) to indoor coverage is a natural inexpensive way of providing network coverage inside the buildings. However, it does not guarantee sufficient link quality required for optimal HSDPA operation. On the contrary, deploying a dedicated indoor system may be far too expensive from an operator's point of view. In this thesis, the concept is laid for the understanding of indoor radio wave propagation in a campus building environment which could be used to plan and improve outdoor-to-indoor UMTS/HSDPA radio propagation performance. It will be shown that indoor range performance depends not only on the transmit power of an indoor antenna, but also on the product's response to multipath and obstructions in the environment along the radio propagation path. An extensive measurement campaign will be executed in different indoor environments analogous to easy, medium and hard radio conditions. The effects of walls, ceilings, doors and other obstacles on measurement results would be observed. Chapter one gives a brief introduction to the evolution of UMTS and HSDPA. It goes on to talk about radio wave propagation and some important properties of antennas which must be considered when choosing an antenna for indoor radio propagation. The challenges of in-building network coverage and also the objectives of this thesis are also mentioned in this chapter. The evolution and standardization, network architecture, radio features and most importantly, the radio resource management features of UMTS/HSDPA are given in chapter two. In this chapter, the reason why Wideband Code Division Multiple Access (WCDMA) was specified and selected for 3G (UMTS) systems would be seen. The architecture of the radio access network, interfaces with the radio access network between base stations and radio network controllers (RNC), and the interface between the radio access network and the core network are also described in this chapter. The main features of HSDPA are mentioned at the end of the chapter. In chapter three the principles of the WCDMA air interface, including spreading, Rake reception, signal fading, power control and handovers are introduced. The different types and characteristics of the propagation environments and how they influence radio wave propagation are mentioned. UMTS transport, logical and physical channels are also mentioned, highlighting their significance and relationship in and with the network. Radio network planning for UMTS is discussed in chapter four. The outdoor planning process which includes dimensioning, detailed planning, optimization and monitoring is outlined. Indoor radio planning with distributed antenna systems (DAS), which is the idea and motivation behind this thesis work, is also discussed. The various antennas considered and the antenna that was selected for this thesis experiment was discussed in chapter five. The antenna radiation pattern, directivity, gain and input impedance were the properties of the antenna that were taken into consideration. The importance of the choice of the antenna for any particular type of indoor environment is also mentioned. In chapter six, the design and fabrication of the monopole antennas used for the experimental measurement is mentioned. The procedure for measurement and the equipment used are also discussed. The results gotten from the experiment are finally analyzed and discussed. In this chapter the effect of walls, floors, doors, ceilings and other obstacles on radio wave propagation will be seen. Finally, chapter seven concludes this thesis work and gives some directions for future work.
Keywords: HSPDA; Indoor; Radio; UMTS